2020
DOI: 10.1134/s1064229320070054
|View full text |Cite
|
Sign up to set email alerts
|

Postagrogenic Changes in the Enzyme Activity and Organic Carbon Content in Chernozem during the First Three Years of Fallow Regime

Abstract: Comprehensive studies of the biological status of ordinary chernozem (Haplic Chernozem (Loamic)) were carried out in the early years of the fallow regime in comparison with its arable analogue, old fallow, and the reference virgin steppe soils. They included a field experiment on the conversion of an oldarable plot with the ordinary chernozem in Botanical Garden of the Southern Federal University to a fallow. In this experiment, organic carbon and the activity of two classes of enzymes, oxidoreductases (catala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 32 publications
(30 reference statements)
0
2
0
Order By: Relevance
“…The firming of soil arising as a result of the work of the heavy equipment used in forest harvesting operations can limit forest productivity seriously for a long time. The impact of the compression on the fertility and the ecological condition of soils was studied extensively, but less information is well known about the recovery of soil properties over time (Azarenko et al, 2020;Kazeev et al, 2020). The recovery of the physical properties of Luvisol and Podzol was shown before, within 54 and 70 years (Mohieddinne et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The firming of soil arising as a result of the work of the heavy equipment used in forest harvesting operations can limit forest productivity seriously for a long time. The impact of the compression on the fertility and the ecological condition of soils was studied extensively, but less information is well known about the recovery of soil properties over time (Azarenko et al, 2020;Kazeev et al, 2020). The recovery of the physical properties of Luvisol and Podzol was shown before, within 54 and 70 years (Mohieddinne et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Changes in landuse may results in changes in morphological pattern of soil profile, composition of soil organic matter and soil physical properties as well as nitrogen and phosphorus re-distribution (Shang et al 2019) and biological properties of soil such as rate of decomposition of OC, enzymatic activity and microorganism community (Telesnina and Zhukov 2019). Kazeev et al (2020) reported that the organic carbon content in the soil of the young fallow increased already in the first year. In addition, changes in the content of organic matter in soils under long-term agricultural use have been broadly studied by many researchers, however fewer studies have an insight into the whole soil profile (Follett et al 2009), and researchers have only rarely compared the soil properties of arable, fallow and virgin soils deeper than 30 to 45 cm.…”
Section: Introductionmentioning
confidence: 99%